Dyskurs edukacyjny oraz problem dyskursywnego konstruowania tożsamości i wiedzy z perspektywy krytycznej i krytycznie zorientowanej analizy dyskursu - Starego, Karolina (Kultura-Społeczeństwo-Edukacja, 2019)
The main purpose of this paper is to present the specific character of educational discourse in terms of the critical (CDA) and critically-oriented discourse analysis (E. Laclau and Ch. Mouffe) and to identify issues and problems that affect research concerning the discursive construction of identity. My main subjects of interest, and the key notions for the discourse-oriented pedagogy, are identity and knowledge. I will try to show how in spite of the relevance of those two notions, the use of discourse analysis in pedagogical research forces us to transcend the narrowly defined disciplinary boundaries. When it is analyzed in a critical manner the thing we call “educational discourse” expands considerably, affecting the scope of both theoretical and research-oriented interests of pedagogy itself. With regard to identity and knowledge, I try to show the inadequacies of the often employed theories of E. Laclau, Ch. Mouffe and M. Foucaul, for analysis of identification processes. I argue that those processes may be successfully analyzed using the CDA framework. The issue of structural constraints that is addressed in CDA, in combination with Laclau’s theory of affective investment allow for a more comprehensive study of the conditions of possibility of the processes of identification.